Innovative Learning Media in Era 4.0: Review - Yanti, Febri (RADINKA JAYA UTAMA PUBLISHER, 2022)
Various learning media innovations continue to grow which acts as a supplement in learning. A good learning media is effective, efficient, shortens the time for delivering teaching materials and can stimulate the imagination of educators when getting factual information through the media. Learning media is designed to provide a real picture of something abstract. The implementation of industry 4.0 can be through various innovative learning media. The use of innovative learning media can be through gadget intermediaries or digitally as a means of connecting conventional learning media into innovative learning media.